NÚMEROS COMPLEXOS: INTER-RELAÇÃO ENTRE CONTEÚDOS E APLICAÇÕES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The Complex Numbers have many applications both in Mathematics and in other areas of knowledge. Associated with other mathematical content, promote alternative techniques demonstration and troubleshooting, rescuing attributing meanings and concepts. There are areas of knowledge that are considered essential and others that are important facilitators of calculations. Nevertheless, the Complex Numbers are little explored or exploited minor in secondary education. This paper aims to present opportunities for integration of Complex Numbers with other mathematical content as well as applications of these numbers in other areas of knowledge, valuing the historical aspects, algebraic and geometric content.
Keywords: Números Complexos; inter-relação; aplicações; complex numbers; interrelationship; applications; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA